Enhanced biochemical and biomechanical properties of scaffolds generated by flock technology for cartilage tissue engineering - Steck, Eric; Bertram, Helge; Walther, Anja; Brohm, Kathrin; Mrozik, Birgit; Rathmann, Jutta Maxi; Merle, Christian; Gelinsky, Michael; Richter, Wiltrud (Tissue engineering, 2010)
Natural cartilage shows column orientation of cells and anisotropic direction of collagen fibers. However, matrices presently used in matrix-assisted autologous chondrocyte implantation do not show any fiber orientation. Our aim was to develop anisotropic scaffolds with parallel fiber orientation that were capable to support a cellular cartilaginous phenotype in vitro. Scaffolds were created by flock technology and consisted of a membrane of mineralized collagen type I as substrate, gelatine as adhesive, and parallel-oriented polyamide flock fibers vertically to the substrate. Confocal laser scan microscopy demonstrated that mesenchymal stem cells (MSCs) adhered and proliferated well in the scaffolds and cell vitality remained high over time. Articular chondrocytes seeded in a collagen type I gel into flock scaffolds deposited increasing amounts of proteoglycans and collagen type II over time. MSC-seeded flock scaffold constructs under chondrogenic conditions deposited significantly more proteoglycans and collagen type II than MSC collagen type I gel constructs only. Biomechanical testing revealed higher initial hardness of flock scaffolds than that of a clinically applied collagen type I/III scaffold combined with superior relaxation and an increasing hardness in MSC-loaded flock biocomposites during chondrogenesis. In conclusion, flock technology allows fabrication of scaffolds with anisotropic fiber orientation that mediates superior biomechanical and biochemical composition of tissue engineering constructs for cartilage repair.
Gesehen am 27.10.2023